2014
DOI: 10.3389/fpsyg.2014.00832
|View full text |Cite
|
Sign up to set email alerts
|

AT1 receptor blockade alters nutritional and biometric development in obesity-resistant and obesity-prone rats submitted to a high fat diet

Abstract: Obesity is a chronic metabolic condition with important public health implications associated with numerous co-morbidities including cardiovascular disease, insulin resistance, and hypertension. The renin angiotensin system (RAS), best known for its involvement in cardiovascular control and body fluid homeostasis has, more recently, been implicated in regulation of energy balance. Interference with the RAS (genetically or pharmacologically) has been shown to influence body weight gain. In this study we investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(55 reference statements)
2
11
0
1
Order By: Relevance
“…The reason for the divergence in adiposity gains between prone and resistant rodents is not known but can be partially explained by increased energy intake and the development of resistance to the actions of leptin, a key regulator of food intake and energy metabolism . Recently, it was shown that losartan, a systemic AT 1 receptor blocker, similarly reduced body weight in rats fed a high‐fat diet whether they were DIO or DR . We also previously showed that the neutral cannabinoid CB 1 receptor antagonist AM4113 reduced body weight that rapidly stabilized at 5 and 10% less than vehicle‐treated rats respectively with a 2 and 10 mg/kg dose .…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the divergence in adiposity gains between prone and resistant rodents is not known but can be partially explained by increased energy intake and the development of resistance to the actions of leptin, a key regulator of food intake and energy metabolism . Recently, it was shown that losartan, a systemic AT 1 receptor blocker, similarly reduced body weight in rats fed a high‐fat diet whether they were DIO or DR . We also previously showed that the neutral cannabinoid CB 1 receptor antagonist AM4113 reduced body weight that rapidly stabilized at 5 and 10% less than vehicle‐treated rats respectively with a 2 and 10 mg/kg dose .…”
Section: Discussionmentioning
confidence: 99%
“…Esses resultados são concordantes com os de estudos prévios que mostram que o tratamento com antagonistas do receptor AT 1 da Angiotensina II é benéfico contra a obesidade e a resistência à insulina 8,12 . Todavia, não alterou o peso da gordura perigonadal das fê-meas obesas, postulando efeitos tecido-específico dessa droga.…”
Section: Discussionunclassified
“…Similar to its effects on blood pressure, losartan has also been shown to attenuate body weight gain in obese and diet-resistant rats fed a high-fat diet (Smith et al 2014). Paraventricular nucleus AT 1a knockout mice fed a high-fat diet have increased adiposity attributable to both increased energy consumption and decreased energy expenditure (de Kloet et al 2013).…”
Section: Angiotensin IImentioning
confidence: 99%